Different Assessment of Plasmin with Different Substrates - Lämmle, B; Duckert, F; with the technical assistance of; Bondeli, Ch; Hänni, L (Thrombosis and Haemostasis, 1980)
The alteration of human and porcine plasmin and the influence of EACA and AMCHA on their activity were investigated. Solutions of both plasmins undergo storage induced alteration, which is best recorded by Chromozym PL, whereas the other chromogenic substrates, S-2251 and S-2302, and casein are less sensitive, and the fibrin plate inadequate. Plasmin amidolytic and fibrinolytic activity is maximally enhanced at 7.6 × 10–3 M EACA and 6.4 × 10–4 M AMCHA, and decay through storage is reversed. The caseinolytic activity seems slightly inhibited at the same EACA and AMCHA concentrations.Our results show:1. The quotient: plasmin activity towards Chromozym PL/Activity towards S-2251 is a useful indicator of "plasmin quality". The quotient decreases markedly upon storage of plasmin solutions.2. Plasmin stability is improved in the presence of AMCHA.3. It is valueless to add EACA or AMCHA to inhibit plasmin in amidolytic assays since the chosen concentration enhances the amidolytic activity of already formed plasmin.
Keywords: Key words; Plasmin; EACA; AMCHA; Storage alteration; Activation; Chromogenic substrates